The psychosocial impact of madrasah infrastructure: A qualitative evaluation of BAZNAS philanthropic program - Hadid, Marwan; Al-Wathani, M. Saddam Kiramuddin Al-Wathani; Sahipudin, Sahipudin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study investigates the intersection of Islamic philanthropy and educational psychology by evaluating the